2022
DOI: 10.1038/s41467-022-31227-1
|View full text |Cite
|
Sign up to set email alerts
|

Islet autoantibody seroconversion in type-1 diabetes is associated with metagenome-assembled genomes in infant gut microbiomes

Abstract: The immune system of some genetically susceptible children can be triggered by certain environmental factors to produce islet autoantibodies (IA) against pancreatic β cells, which greatly increases their risk for Type-1 diabetes. An environmental factor under active investigation is the gut microbiome due to its important role in immune system education. Here, we study gut metagenomes that are de-novo-assembled in 887 at-risk children in the Environmental Determinants of Diabetes in the Young (TEDDY) project. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 81 publications
(109 reference statements)
0
11
0
Order By: Relevance
“…Generalized linear mixed model (GLMM) analysis was performed using the glmmTMB package (Version 1.1.2.3) in the R environment (version 3.6.2) . DPI and treatment groups (infected, uninfected, and isoproterenol treatment) were set as fixed effects, while the mouse ID was set as a random effect . The probability distribution and link function of the GLMM models were set to Gaussian and identity, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Generalized linear mixed model (GLMM) analysis was performed using the glmmTMB package (Version 1.1.2.3) in the R environment (version 3.6.2) . DPI and treatment groups (infected, uninfected, and isoproterenol treatment) were set as fixed effects, while the mouse ID was set as a random effect . The probability distribution and link function of the GLMM models were set to Gaussian and identity, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Fungal taxa were not related to first islet autoantibodies [81]. Metagenome‐assembled genomes (MAGs) in 887 TEDDY children followed longitudinally revealed 883 species, including 176 previously undescribed human microbiome species [82]. Metagenome assemblies based on protein families were examined for association with the appearance of islet autoantibodies.…”
Section: First‐appearing Autoantibody and Exposuresmentioning
confidence: 99%
“…Metagenome assemblies based on protein families were examined for association with the appearance of islet autoantibodies. Results showed that 2373 MAGs were positively and 1549 negatively associated with IA[82]. A possible MAGs dichotomy of IAA‐and GADA first remains to be determined.…”
Section: First‐appearing Autoantibody and Exposuresmentioning
confidence: 99%
“…This evidence came from a Finnish study in which a reduction in microbiota richness was detected in children who develop T1D prior to diagnosis but after seroconversion [ 80 ]. Moreover, the seroconversion has been positively correlated with the increase of lipopolysaccharides biosynthesis in Bacteroides genome and sulfate reduction in Anaerostipes genome [ 81 ].…”
Section: Gut Microbiota Dysbiosis In T1dmentioning
confidence: 99%